The brain-heart connection: An investigation of cardiovascular autonomic alterations following mild traumatic brain injury - Thorne, Jacinta Louise (Curtin University, 2024)
This PhD thesis used novel symptom-based clinical profiles, clinical assessments, and advanced neuroimaging to investigate cardiovascular autonomic alterations following mild traumatic brain injury (mTBI). Mood and autonomic clinical profiles were associated with higher resting heart rate and poorer recovery, suggesting that autonomic dysregulation may contribute to persisting symptoms. The normal regulatory relationship between resting heart rate and cerebral blood flow was disrupted in some people following mTBI, providing insight into the neurobiological basis of cardiovascular alterations.